The Effect of Atonic Growth Regulatory Substances on the Growth and Yield of Mustard Greens (Brasica rapa L.) Using Black Soil - Saiful Arifin; Muhammad Burhanudin Adenan; Intan Rohma Nurmalasari (Nabatia, 2023)
This study aims to determine the correct dose of atonic plant regulators and black soil doses on the growth and production of mustard greens. This research was conducted from March 2023 to May 2023, using a factorial Randomized Block Design (RBD), namely the concentration of atonic growth regulators, which consisted of 4 dose levels, namely 0ml, 3ml, 5ml, 7ml, and black soil, which consisted of 3 levels i.e. 0 gram, 5 ton/h, 10 ton/h. With 3 replications resulting in 36 experimental units. Observational variables consisted of plant height, number of leaves, root length, fresh weight, dry weight, and harvest index. Data were analyzed using analysis of variance (ANOVA) then continued with the Honest Significant Difference Test. The results of this study explained that there were changes in the observations observed both from plant height, number of leaves, root length, and dry weight with atonic growth regulators as growth stimulants for pakcoy mustard plants. And black soil to improve soil nutrients